Influencing factors of bentonite for the directional electric repair of landfill HDPE membrane leakage in calcium ion solution - Guangyuan Yao; Yuqiang Liu; Ya Xu; Jingcai Liu; Can Qian; Yanmei Yang; Zhu Liang; Minsong Lin (Waste Management Bulletin)
The timely repair of high-density polyethylene (HDPE) membrane leakage in landfills is an important means of environmental risk control, which is critical for preventing leachate from polluting groundwater and soil. Electric repair technology is expected to become a hot spot in the leakage repair of HDPE films, because it can solve the issues of complex operation, high costs, and security risks during the operation and closure of landfills. To explore the influence law of various technical factors on the electric repair process, we carried out single factor experiments on the main influencing factors such as the operation time, bentonite concentration and dispersant/bentonite dosage ratio, leakage size, and calcium concentration. We then explored the best technological conditions. The results showed that accumulation at the leakage site possessed a good repair effect with a permeability coefficient of 4.22 × 10−6 cm/s. Furthermore, we observed that the Zeta potential played an important role in the electric repair technology, where the higher the absolute value of the Zeta potential, the faster the electrophoretic migration rate of the bentonite particles, and the lower the permeability coefficient of accumulation. This study may serve as a theoretical basis and offer scientific guidance for the directional electric repair of HDPE membrane leakage during the operating period and after the closure of landfills.